PENENTU KESEHATAN PERBANKAN - YULIUS KURNIA SUSANTO; TJHAI FUNG NJIT (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
This research aims to provide empirical evident about determinant on banking healthy using the CAMEL (capital, assets, management, earnings and liquidity) method. CAMEL is one method to evaluate the banking performance. Sample are used in this research all company of state own bank, foreign exchange bank, and non-foreign exchange bank from the directory from 2005 until 2007 using purposive sampling method. The result of this research shows that nonperformance loan, return on equity, loan to deposit ratio and reserve requirement have determinant on banking healthy.